2008
DOI: 10.1016/j.amjcard.2007.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Adult-Onset Asthma to Coronary Heart Disease and Stroke

Abstract: Asthma has been associated with atherosclerotic disease in several studies with some evidence that this association may be limited to women. However, most previous studies have failed to account for the heterogeneity of asthma subtypes. We previously reported increased carotid intima medial thickness among women with adult-onset asthma. In this study, we examine the association of adult and child-onset asthma with incident coronary heart disease (CHD) and stroke. Subjects were classified according to self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 28 publications
9
102
2
3
Order By: Relevance
“…Several epidemiologic studies showed that adult-onset asthma (age of onset X21 years) in particular is associated with cardiovascular diseases, 28 carotid atherosclerosis, 29 coronary heart disease or stroke. 28 Asthma may predispose an individual to atherosclerosis through specific pathobiologic pathways, perhaps linked to the chronic inflammatory responses of this disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several epidemiologic studies showed that adult-onset asthma (age of onset X21 years) in particular is associated with cardiovascular diseases, 28 carotid atherosclerosis, 29 coronary heart disease or stroke. 28 Asthma may predispose an individual to atherosclerosis through specific pathobiologic pathways, perhaps linked to the chronic inflammatory responses of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…28 Asthma may predispose an individual to atherosclerosis through specific pathobiologic pathways, perhaps linked to the chronic inflammatory responses of this disorder. Alternatively, the association between asthma and atherosclerosis may be caused by an inherent joint susceptibility to both diseases through shared inflammatory pathways and genetic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these diseases (obesity, diabetes, asthma, allergies, arthritis and chronic joint disease, dementia, and cardiovascular disease) have a substantial infl ammatory component ( 3-6 ) with notable cooccurrences ( 7,8 ). Perhaps no changes in the modern diet have had a greater impact than the quantitative and qualitative changes in fat consumption.…”
mentioning
confidence: 99%
“…It is postulated to be due to the effect of sex hormones in women [2] . Studies have shown that women with adult onset asthma have increased risk of coronary heart disease and stroke [3] . The usual symptoms of asthma are generally present with varying degrees of breathlessness, wheeze and cough in adult onset asthma also.…”
Section: Introductionmentioning
confidence: 99%